(Diisopropylammonium)2MnBr4: a multifunctional ferroelectric with efficient green-emission and excellent gas sensing properties. Issue 44 (19th April 2017) - Jiang, Chunli; Zhong, Ni; Luo, Chunhua; Lin, Hechun; Zhang, Yuanyuan; Peng, Hui; Duan, Chun-Gang
Abstract : A luminescent ferroelectric, (diisopropylammonium)2 MnBr4, is prepared, which exhibits efficient green emission, a high T C value and excellent alcohol vapor sensing properties. Abstract : Combination of excellent optical properties and ferroelectricity of hybrid materials leads to high-performance optoelectronic devices. Here we present a new organic–inorganic hybrid compound (diisopropylammonium)2 MnBr4 (DIPA2 MnBr4 ) which shows high temperature ferroelectricity accompanied by highly efficient green-light emission. DIPA2 MnBr4 also exhibits sensitive and selective optical response to alcohol vapors.